Action relevance in linguistic context drives word-induced motor activity - Aravena, Pia; Courson, Melody; Frak, Victor; Cheylus, Anne; Paulignan, Yves; Deprez, Viviane; Nazir, Tatjana (Frontiers in Human Neuroscience, 2014)
Many neurocognitive studies on the role of motor structures in action-language processing have implicitly adopted a “dictionary-like” framework within which lexical meaning is constructed on the basis of an invariant set of semantic features. The debate has thus been centered on the question of whether motor activation is an integral part of the lexical semantics (embodied theories) or the result of a post-lexical construction of a situation model (disembodied theories). However, research in psycholinguistics show that lexical semantic processing and context-dependent meaning construction are narrowly integrated. An understanding of the role of motor structures in action-language processing might thus be better achieved by focusing on the linguistic contexts under which such structures are recruited. Here, we therefore analyzed online modulations of grip force while subjects listened to target words embedded in different linguistic contexts. When the target word was a hand action verb and when the sentence focused on that action an early increase of grip force was observed. No comparable increase was detected when the same word occurred in a context that shifted the focus towards the agent’s mental state. There mere presence of an action word is thus not sufficient to trigger motor activation. Moreover, when the linguistic context set up a strong expectation for a hand action, a grip force increase was observed even when the tested word was a pseudo-verb. The presence of a known action word is thus not required to trigger motor activation. Importantly, however, the same linguistic contexts that sufficed to trigger motor activation with pseudo-verbs failed to trigger motor activation when the target words were verbs with no motor action reference. We argue that motor structure activation is part of a dynamic process that integrates the lexical meaning potential of a term and the construction of a situation model.